Sustainable catalytic processes - Saha, Basudeb; Fan, Maohong; Wang, Jianji (Elsevier, 2014)
The development of catalysts is the most sophisticated art in chemical sciences. It can be read like a story book when the critical scientific contents are presented in a chronological manner with short and simple sentences. This book will meets these criteria. To address the sustainability issues of existing chemical manufacturing processes or producing new chemicals, researchers are developing alternate catalysts to eliminate toxic chemicals use and by-products formation. Sustainable Catalytic Processes presents critical discussions of the progress of such catalytic development. This book of contemporary research results in sustainable catalysis area will benefit scientists in both industries and academia, and students to learn recent catalysts/process development.